Electoral Reforms for Inclusive Representation: Accessing The Legal Rights of Minority in Nigerian Politics - Ogedengbe, John Afolabi (Fakultas Hukum Universitas Lampung, 2024)
Nigeria as a multi ethnic society is repeatedly plagued with the cries for more inclusive representation and participation from minority groups. An attempt in creating a more balanced perception of inclusiveness has produced the federal character principle which is to be applied in political appointments and across federal agencies with the aim at addressing ethnic-related concerns. Despite this step taken in curing this supposed biased, there still remains unsatisfied clamors for more inclusive representation by other minority groups in politics. This article aims to critically examines the necessity of electoral reforms in Nigeria, with a focus on the legal rights of minority groups within the political landscape to promote more inclusive representation. Flowing from the aim, it further examines the current challenges faced by minority communities in Nigeria as to active political participation, and inclusivity in governance. In evaluating the ripple effects of this lack of inclusive representation, on Nigeria politics, doctrinal research methodology was adopted herein as the work examine the Nigerian Constitution and other legal framework pertaining to Elections and the for Electoral Reform in Nigeria. The article founds that there has been a lot of bias in the political landscape of the Country, and such needed to be holistically looked into. Lessons were drawn from Rwanda regarding the inclusive democracy they practice. The article recommends comprehensive reforms focused on ensuring fair representation through legislative measures and adjustments to the electoral system. It also emphasizes the need for a redefined electoral landscape that amplifies the voices of minorities, promotes diversity, and strengthens the nation's democratic foundation.